C3 glomerulopathy associated with mycoplasma pneumoniae infection and positive IgA staining - Zhi-Yu Duan; Ji-Jun Li; Guang-Yan Cai; SuXia Wang; XuanLi Tang; WanYin Hou; Lei Jiang; Yan Song (BMC Nephrology)
Abstract Background Patients with C3 glomerulopathy (C3G) often have a history of infection, which implies that infection may lead to abnormal activation of the complement alternative pathway (CAP) and induce the development of C3G. However, patients with postinfectious glomerulonephritis (PIGN) often have a low serum C3 concentration and positive glomerular C3 staining, consistent with the activation of the CAP. PIGN, especially if it involves simultaneous IgA deposition, is often difficult to differentiate from C3G. Case Presentation In this study, we report the consequences of Mycoplasma pneumoniae (MP) infection in a 66-year-old male Chinese patient, who developed persistent hypocomplementemia, gross hematuria, and rapidly progressive glomerulonephritis. The findings of the histologic examination of an initial renal biopsy were consistent with a diagnosis of IgA-dominant postinfectious glomerulonephritis. The sample was negative for Gd-IgA1 staining. After treatment with antibiotics, glucocorticoids, and mycophenolate mofetil, the patient’s serum creatinine decreased from a peak of 387 µmol/L to 195 µmol/L prior to discharge, and there was a partial response in his urinary protein concentration. After 2 months, his serum C3 concentration had returned to normal. However, owing to reinfection with MP the patient’s serum creatinine rapidly increased again to 475.07 µmol/L, and this was accompanied by a decrease in serum C3 concentration (> 8 months) and positivity for C3 nephritis factor. Examination of both renal biopsies showed stronger immunostaining for C3 than for IgA in the glomeruli. Conclusion Thus, MP infection can cause sustained activation of the CAP, leading to C3G. For patients with MP infection, if there is an ongoing decrease in complement C3 levels and a progressive increase in serum creatinine, it is crucial to be vigilant for possible C3G and to consider the use of immunosuppressive therapy in conjunction with anti-infective treatment to prevent the ongoing activation of the CAP.